Task based method to reinforce english vocabulary for first semester students from pedagogy of national and foreign languages major, UPSE - Basante Morante, Ana Julia (2022)
The current research project attempts to improve the English vocabulary knowledge of the 73 students of first semester students of Pedagogy of National and Foreign languages Major 2021-2s – Universidad Estatal Peninsula de Santa Elena by creating and proposing an activity booklet focused on the Task-Based Method. In the educational setting, this method aims at using tasks as the medium of introduction to new vocabulary, its definition and grammatical use. To accomplish the purpose and its proposal, the quantitative method was used, which allowed the researcher to apply the survey technique. The analyzed information helped to understand better the students' needs in reinforcing their English vocabulary. This paper suggests a set of task-based vocabulary activities based on the level of the students and topics of interest. Furthermore, these were designed to provide students with a tool to help them with autonomous learning of the target language and that seeks to decrease the gaps in the teaching-learning process and encourage learners to put new words into practice while developing their English skills.